Empathizing. A sharing of life - Fughelli, Patrizia; Zompatori, Maurizio (Medicina Historica, 2019)
Nobody ignores the importance of proper communication with the patient so that it can be considered an integral part of it and maybe the very beginning of the cure. However not everyone considers how difficult is it to handle this. Our paper focuses on the fact that the doctor’s contribution is not to let the truth come to light “tout court”, taking priority above everything, but only to provide the biographical mosaic with some pieces that the patient can recognize as true and useful. When illness and death are not just words, but already quite near us, self-knowledge is the only thing that makes life alive forever. You cannot pass through the disease without changing. Not always and not necessarily this is for the better, but often it brings awareness.